Mineral Imbalances in the Complex Interactions Soil-Plant-Animal in the Grasslands of Center-West Region of the São Paulo State, Brazil - de Carvalho, Paulo Reis (Pakistan Journal of Nutrition, 2009)
This study was conducted to analyze the mineral composition of forage plants used for beef cattle in nine regions between the years 1984-1992 and clinical observations of animals stretched to date (2009). The forage Brachiaria decumbens used in cutting farm was studied during the four seasons of the year writing the collection of sampling the twelve months of the year. We used a completely randomized design with three replicates per season and each of the nine municipalities studied, resulting in the total sample of 108 samples of forage grasses to evaluate the behavior of the macroscopic Ca, P and Mg and trace elements Cu, Zn, Fe, Mn and Co from the analysis by atomic absorption spectrophotometry, except the P by molecular absorption spectrophotometry of forage available for grazing cattle during the seasons spring, summer, autumn and winter. Still, we sampled animal tissue (liver) and soil to determine the mineral profile. The percentage variation in averages were: Macro 0.36-0.40 g% Ca, 0.05-0.10 g% P, 0.14-0.20 g% Mg. Microminerals: 30-40 mg% Zn, 3-8 mg% Cu, 0.06-0.09 mg% Co and 40-80 mg% Mn. These results showed that when adjusting the requirements of protein and energy supplementation through matter, all small macro: Ca, P and Mg and trace elements Cu, Co and Zn must also be supplemented at all times or the seasons second category animal growth, reproduction and lactation. The concentration of macro: 485.33 mg% Ca: 9011.11 mg% P, 317.17 mg% Mg and trace minerals in liver varied: 152.38 mg% Cu, 219.67 mg% Zn, 6.36 mg% Mn; 260.18 mg% Fe and 0.132 mg% Co. The main clinical signs and symptoms observed in the properties: fibrous osteodystrophy, rickets, osteomalacia , infertility, excitability, loss of appetite, anemia, reduced growth, Achromotrichia, heart failure, bones that are fragile and easily fractured, diarrhea, infertility and anestrus, low fertility, abortion, stillbirth and low birth weight, lesions of parakeratosis and tetany pastures. Clinical signs of deficiencies of macro and micro minerals in the animals ceased with the effect of mineral supplementation led to animals with deficiencies of macro and trace elements in forage diagnosed.